2019
DOI: 10.3389/fpubh.2019.00238
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of the “POD Adventures” Smartphone Game: A Blended Problem-Solving Intervention for Adolescent Mental Health in India

Abstract: Introduction: Digital technology platforms offer unparalleled opportunities to reach vulnerable adolescents at scale and overcome many barriers that exist around conventional service provision. This paper describes the design and development of POD Adventures , a blended problem-solving game-based intervention for adolescents with or at risk of anxiety, depression and conduct difficulties in India. This intervention was developed as part of the PRemIum for ADolEscents (PRIDE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 48 publications
3
62
0
Order By: Relevance
“…As this was a pilot study with the primary goal of determining feasibility and acceptability of the training programs and to inform improvements to the instructional content and delivery of the training programs, we did not conduct an in-depth thematic analysis of the qualitative data. Rather, we followed guidance from the person-based approach to intervention development [ 33 , 62 ], which enabled the combination of quantitative and qualitative data to inform modifications to the training programs. Specifically, we used a framework analysis approach [ 63 ] to guide our identification of common topics within the qualitative data, following a coding framework with the four core domains outlined from the satisfaction and acceptability questionnaire (i.e., appropriateness, acceptability, adoption, and feasibility) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this was a pilot study with the primary goal of determining feasibility and acceptability of the training programs and to inform improvements to the instructional content and delivery of the training programs, we did not conduct an in-depth thematic analysis of the qualitative data. Rather, we followed guidance from the person-based approach to intervention development [ 33 , 62 ], which enabled the combination of quantitative and qualitative data to inform modifications to the training programs. Specifically, we used a framework analysis approach [ 63 ] to guide our identification of common topics within the qualitative data, following a coding framework with the four core domains outlined from the satisfaction and acceptability questionnaire (i.e., appropriateness, acceptability, adoption, and feasibility) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, prior studies have demonstrated promising findings using digital technology to support task-sharing mental health services in low-resource settings through the use of digital tools for diagnosis, guiding clinical decision making, and facilitating supervision [ 25 ]. Specifically in India, recent studies have reported on a successful digital decision-support platform for supporting community health workers and primary care providers in the screening, diagnosis, and management of common mental disorders [ 31 ]; the use of an Android app with tailored video content for training community volunteers about mental health, connecting individuals with available services, and raising awareness [ 32 ]; and the initial feasibility and acceptability of a digital game accessible from a smartphone app involving a problem-solving intervention for adolescent mental health [ 33 ]. These studies highlight the viability and promise of digital interventions for mental health in low-resource settings such as India; however, there remains an immediate need to generate evidence on the feasibility, acceptability, and potential effectiveness of using a fully remote digital training program delivered on a smartphone application to non-specialist health workers in a rural area of a low-resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…By employing a collaborative person-centered approach, it was possible for the researchers to optimize various features throughout the development of this digital game-based mental health intervention. This included simplification of language to meet the needs of a lower literacy student population, accommodating the need for offline access to the digital intervention content given the poor Internet connectivity in the region, incorporating sufficient risk assessment and management features into the mobile app to respond to participants' low mood, and the inclusion of low-intensity human support to offer instruction and personalized support to participants as they complete the game (9).…”
Section: Designing Technologies For Youth Mental Healthmentioning
confidence: 99%
“…The workshops provided further opportunities for the end-users to engage with and discuss ways to optimise the delivery of the intervention-integrated survey in ways that would work for them. Previous studies 24,25,30,31 that engaged with young people in developing digital interventions have also identified that using co-design processes has highlighted the value of usercentred design that allowed for meaningful engagement and enabled focus on user need. For example, Nakarada-Kordic et al (2017) 31 conducted co-design sessions to develop an online resource for young people experiencing psychosis and found that participants discussed matters that were not expected by clinicians.…”
Section: Discussionmentioning
confidence: 99%